Biological potential of puffballs: A comparative analysis. (March 2016) - Petrović, Predrag; Vunduk, Jovana; Klaus, Anita; Kozarski, Maja; Nikšić, Miomir; Žižak, Željko; Vuković, Nebojša; Šekularac, Gavrilo; Drmanić, Saša; Bugarski, Branko
Highlights: Methanol extracts of investigated puffballs exhibited high antioxidant activity. Different chemical fractions were correlated with antioxidant abilities. β-glucans made up over 80% of total sugar content. Mosaic and pestle puffball showed selective cytotoxicity toward tumor cell lines. Extracts acted as ACE-inhibitors at relatively low concentration. Abstract: Handkea utriformis (HU), H. excipuliformis (HE) and Vascellum pratense (VP) mature fruiting bodies methanol extracts were tested for biological activities and active compounds. The extracts showed prominent radical scavenging, reducing, antioxidative and chelating abilities. Scavenging ability was correlated with phenolic (ABTS assay) or phenolic and/or sugar/β-glucan content (DPPH). Antioxidative and Fe 3+ -reducing ability of VP extract was the highest, and was best correlated with flavonoid content. The same extract exhibited the best angiotensin-converting enzyme inhibitory activity. HU and HE showed selectivity toward tumor cell lines in cytotoxicity analysis. The extracts exhibited various antimicrobial activity, the best being against Listeria monocytogenes (HE, MIC-0.625 mg/mL); fatty acid content was particularly high in HU (37.25 mg/g), with linoleic acid making up more than 57% in all samples. Phenolics were present in considerable amount, as well as β-glucans (HU, 16.67%). Although these mushrooms are inedible after autolysis process, they were still a good source of biologically active products.